2016
DOI: 10.1002/pon.4180
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, self‐efficacy and self‐esteem in breast cancer survivors: a panel model

Abstract: Purpose Physical activity (PA) has been consistently associated with improved self-esteem in breast cancer survivors. However, this relationship is poorly understood. The purpose of this study was to examine whether changes in PA and self-efficacy influenced changes in self-esteem in breast cancer survivors across six-months. Increases in PA were hypothesized to result in increases in self-efficacy which were hypothesized to influence increases in physical self-worth and global self-esteem. Methods Breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 37 publications
(39 reference statements)
3
27
0
1
Order By: Relevance
“…The post‐hoc analysis revealed that patients with breast/female genital cancer showed significantly lower mean scores (n = 86, M = 1.98) than those with cancer in digestive organs (n = 115, M = 2.58) for the item “changes in appetite” ( P < .0001, partial η 2 = 0.07), but significantly higher scores ( M = 1.07 vs M = 0.64) for the item “worthlessness” ( P < .05, partial η 2 = 0.03). These findings are in accordance with the literature reporting that patients with breast cancer reveal an effect on their self‐esteem …”
Section: Resultssupporting
confidence: 93%
“…The post‐hoc analysis revealed that patients with breast/female genital cancer showed significantly lower mean scores (n = 86, M = 1.98) than those with cancer in digestive organs (n = 115, M = 2.58) for the item “changes in appetite” ( P < .0001, partial η 2 = 0.07), but significantly higher scores ( M = 1.07 vs M = 0.64) for the item “worthlessness” ( P < .05, partial η 2 = 0.03). These findings are in accordance with the literature reporting that patients with breast cancer reveal an effect on their self‐esteem …”
Section: Resultssupporting
confidence: 93%
“…For each item, participants indicated their level of agreement with a given statement according to a four-point Likert-type scale where response options ranged from “Strongly Agree” to “Strongly Disagree.” Example items include, “I feel I do not have much to be proud of” and “I wish I could have more respect for myself.” Higher scores on the RSES indicate higher global self-esteem. This scale is widely used in research on women with breast cancer (e.g., Awick, Phillips, Lloyd, & McAuley, 2016; Schroevers, Ranchor, & Sanderman, 2006), and demonstrated high internal reliability within this sample, α = .89.…”
Section: Methodsmentioning
confidence: 84%
“…Furthermore, we added a new item ( Good environment and facilities ) reflecting respect from the perspective of one's milieu. Previous studies have indicated that a respectful clinical or treatment setting is beneficial for developing and maintaining good self‐esteem and mental health among women with breast cancer …”
Section: Discussionmentioning
confidence: 99%